Virologic and immunologic responses of patients on highly active antiretroviral therapy in a rural community health centre in Limpopo, South Africa: A retrospective study - Aniekan Edet; Henry A. Akinsola; Pascal O. Bessong (AOSIS, 2019)
Background: South Africa has a high HIV burden. Despite increased uptake of persons living with HIV into the South African national antiretroviral therapy programme, the incidence of HIV increased between 2013 and 2016. Studies suggest that increased community viral suppression results in reduced HIV incidence in that community 'independent of unsafe sexual behaviours and sharing used syringes'. Objective: The aim of this study was to investigate the viral and immunologic responses of patients, in a rural community health centre in South Africa, to combination antiretroviral therapy (cART) between January 2004 and July 2016. Methods: This was a retrospective medical record review conducted in Thohoyandou Community Health Centre. Data analysis was done using SPSS 24.0 and Microsoft Excel. The estimates used were 95% confidence intervals, and a p-value < 0.05 was considered to be statistically significant. Results: Analysis was done using 1247 individuals, with 76% of the cohort being female and 98% first-line cART. The proportion of patients with a suppressed viral load (VL) at 6 months post-treatment was 64%, and 72% at 60 months. Fifty-nine per cent had consistent viral suppression over a 6-month period and 14% over at least 54 months. The mean CD4+ cell count at baseline was 227 cells/µL, and 538 cells/µL at 60 months. Multivariate regression analysis revealed that males had poorer immunologic and virologic responses. Conclusions: Viral suppression in the study population was inferior to the UNAIDS target of 90%. The sustainability of viral suppression, once attained, was also low. These may have a negative impact on HIV transmission.